Effect of Kernel Size and Mill Type on Protein, Milling Yield, and Baking Quality of Hard Red Spring Wheat. Issue 1 (19th January 2015) - Baasandorj, Tsogtbayar; Ohm, Jae‐Bom; Manthey, Frank; Simsek, Senay
ABSTRACT: Optimization of flour yield and quality is important in the milling industry. The objective of this study was to determine the effect of kernel size and mill type on flour yield and end‐use quality. A hard red spring wheat composite sample was segregated, based on kernel size, into large, medium, and small kernels, as well as unsorted kernels. The four fractions were milled in three roller mills: Brabender Quadrumat Jr., Quadrumat Sr., and Bühler MLU‐202 laboratory mills. Large kernels had consistently higher flour yield than small kernels across mills, with the Quadrumat Jr. mill showing the lowest flour yield. Mill type and kernel size significantly affected variation in flour protein molecular weight distribution. When compared with larger kernels, flour milled from the small‐kernel fraction contained a higher gliadin fraction and SDS‐unextractable high‐molecular‐weight polymeric proteins, which had positive correlations with bread loaf volume ( r = 0.61, P < 0.05) and mixograph peak time ( r = 0.84, P < 0.001). Overall, small kernels could contribute to enhancing flour breadmaking quality while having a detrimental effect on milling yield.